Factitious disorder in a Vietnamese woman imposed on her 2-month - old child: a rare case report with complicated socio - cultural implications - Tran, Nhu Minh Hang; Nguyen, Huu Cat; Nguyen, Vu Quoc Huy; Clayton, Chau (Tạp chí Y Dược Huế, 2025)
Factitious disorder imposed on another (FDIA) is a psychiatric disorder in which a patient causes physical or psychological signs or symptoms or injuries in her/his child or dependent in order to intentionally deceive others. If not detected in time, a child or dependent’s safety may be at risk. Presented here is a case study of a Vietnamese 26- year - old woman with FDIA, with a history of psychological violence and associated trauma, and the progression of her treatment. With this case, we would like to emphasize the profound impact of socio-cultural factors on the formation of disorders in patient. Patient presented with complaints about bleeding in her infant daughter. After several evaluations the patient was diagnosed with FDIA with co-morbid depressive symptomatology. Patient was treated with sertraline 50mg/day combined with Cognitive Behavior Therapy (CBT) for 12 weekly sessions and family therapy for 4 sessions. Patient had a good treatment progression with a marked reduction of symptoms. At the end of the treatment this patient was able to appropriately care for her infant. While FDIA is thought to be a difficult disorder to treat, often requiring years of therapy and support, in this case the patient progressed rapidly. It is important to treat both depressive symptoms as well as co-morbid psychiatric disorders, in addition to other psychological factors such as conflicts in the family, trauma events in the life, which should not be neglected in assessing the patients with FDIA and psychotherapies such as CBT and family therapy may be effective in this group of patients.